2000
DOI: 10.1080/00140130050084905
|View full text |Cite
|
Sign up to set email alerts
|

Team situation assessment and information distribution

Abstract: Described is the cooperative work of constructing team situation awareness within two teams of a military command and control unit. Specifically discussed is how the distributed cognitive and cooperative work of decision-making of the two teams is structured. The situation enabled two different ways of distributing information within the team: one serial and one parallel. One team chose the parallel information transfer, the other the serial one. Discussed is the interaction patterns that emerge in the respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(56 citation statements)
references
References 10 publications
0
56
0
Order By: Relevance
“…Other research on situation awareness focuses on how the arrangement of equipment and physical layout of the task environment influence access to information and coordination of activities among group members (Artman, 2000). Displays and artefacts that can be readily seen and evaluated by group members create a greater degree of shared awareness.…”
Section: Links Between Awareness and Physical Spacementioning
confidence: 99%
“…Other research on situation awareness focuses on how the arrangement of equipment and physical layout of the task environment influence access to information and coordination of activities among group members (Artman, 2000). Displays and artefacts that can be readily seen and evaluated by group members create a greater degree of shared awareness.…”
Section: Links Between Awareness and Physical Spacementioning
confidence: 99%
“…Artman (2000) showed that for the development of SA in a team, it is preferable that information is provided sequentially in order to allow time for every team member to develop their own SA. Pascual et al (1999) highlight the importance of regularly updating each other in a team, to develop a shared understanding of a situation.…”
Section: The Role Of (Situational) Awareness and Information In Team mentioning
confidence: 99%
“…Many studies show that the quality of communication or information sharing has a relation with team performance (Artman 2000;Pascual et al 1999;Stammers and Hallam 1985). Artman (2000) showed that for the development of SA in a team, it is preferable that information is provided sequentially in order to allow time for every team member to develop their own SA.…”
Section: The Role Of (Situational) Awareness and Information In Team mentioning
confidence: 99%
“…This process of adaptation is also consistent with activity theory (Leontev, 1990) or how a team internalizes new information in terms of information distribution across team members (cf. Artman, 2000).…”
Section: Team Cognitionmentioning
confidence: 99%